Efektivitas Pemberian Sari Kacang Hijau Terhadap Peningkatan Volume Asi pada Ibu Nifas di Praktek Bidan Mandiri Kota Palangka Raya - Yuniarti Yuniarti (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2020)
Background the cause of breast milk does not come out due to stress factors, even malnutrition. The amount and quality of Mother's food greatly affects the amount of breast milk produced. Breastfeeding mothers are strongly encouraged to obtain additional nutrients for breastmilk production and maternal energy. One of them is green beans as a food that is useful as a facilitator of breast milk production.Research objectives to identify the effectiveness of green bean extract on increasing breast milk volume in postpartum mothers. Research methods this study was a pre-experimental design using the one group pre post test design. This research was conducted from April-Oktober 2019. The study population was postpartum mothers who gave birth at PMB Palangka Raya. The sample is 33 respondents. Data analysis using paired t-test.Results the average volume of ASI before administration of mung bean extract was 56.82 ml. The average volume of ASI after the intervention of breast milk volume was 69.55 ml. The difference in the average volume of breast milk before and after being given green bean juice drinks was 12.424 ml. The statistical test results paired t-test show the value of p value = 0.001 is smaller than the value of α (0.05) which means there are significant differences.Conclusion Green bean extract is effective against increasing breast milk volume in postpartum mothers.